Fiqh of Worship in the Life of Millennial Muslims: Overcoming Challenges in Carrying Out Worship in the Midst of Busyness - Marlina; Pitri, Alisya (Zabags International Journal of Islamic Studies, 2025)
This study aims to explore the challenges faced by millennial Muslims in performing acts of worship, particularly fiqh ibadah, amidst the busyness of modern life. The research problem in this study is how millennial Muslims overcome challenges in performing worship, such as prayer, fasting, and zakat, given the demands of work and social life. This study employs a qualitative approach using in-depth interviews and participatory observation with several millennial Muslims in urban areas. The findings indicate that, although work commitments and a fast-paced lifestyle pose obstacles, many of them adapt their worship times with flexibility, such as using technology to remind them of prayer times and learning fiqh ibadah online. Additionally, most respondents highlighted the importance of community in supporting consistent worship practices. The implications of this study are the need for the development of a more relevant da’wah approach that meets the needs of the times, as well as support from educational and religious institutions to provide understanding that is easier for the millennial generation to apply in their worship.